Application of Musa acuminata mediated iron oxide nanoparticles in the removal of sunset yellow dye - M.N. Nafisa Begam; K. Muthukumaran; P. Thamarai (Desalination and Water Treatment)
This study deals with the biogenic preparation of iron oxide nanoparticles (MION) by employing the Musa acuminata pseudostem extract. The morphological aspects of MION were investigated using SEM and HR-TEM, revealing its spherical shape and size of 20 - 60 nm. The MION’s XRD spectra further supported their size to be 20 nm. The FTIR spectrum depicted the presence of phytochemicals in Musa acuminata pseudo stem extract. Antibacterial studies were performed to assess MION’s biocompatibility. The MION was subjected to remove sunset yellow FCF dye solution and batch adsorption parameters like pH (3.0), contact time (180 min), MION dosage (4 mg/100 mL) and initial dye concentration (15 mg/L) were optimized. It was also ascertained that the Freundlich isotherm and pseudo-first-order kinetics were found to be best fit with a maximum adsorption capacity of 8.93 mg/mg, respectively. The thermodynamic findings indicated that MION's adsorption process exhibited spontaneity and endothermicity. The effect of ionic strength and humic acid resulted in a corresponding enhancement and reduction in the removal efficacy for sunset yellow adsorption. The recyclability of MION exhibited consistent performance over five successive cycles with a 75.4% sunset yellow recovery rate. Therefore, MION is cost-effective and efficient in removing toxic dye pollutants.